Микротрон - инжектор синхротрона 1,5 Гэв - Визирь В. А.; Миненко Л. И. Леонтий Иванович; Непокрытых Ю. А.; Сыркин Б. В.; Чучалин И. П. Иван Петрович; Шивырталов М. Т.; Щанин П. М.; Юшков Ю. Г. Юрий Георгиевич; Диденко А. Н. Андрей Николаевич (1966, 1966)
В фонде НТБ ТПУ отсутствует